Upaya Meningkatkan Kemampuan Berhitung Menggunakan Teknik Penguatan Positif Dengan Media Permainan Dakon - Imamah, Syafa'atul; Hasanah, Muhimmatul (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Mathematics is a very basic science tool. Counting skills are part of mathematics that can develop children's cognitive abilities and logical thinking skills. This program aims to determine the effectiveness of dakon media and positive reinforcement techniques in improving counting skills in subjects. The research method used is quantitative using a single-case experimental design. The conclusion in this study is the use of traditional dakon games and positive reinforcement techniques can improve counting skills in subjects with a gain score of 50.